Studying Typography Used in Ability "Rashomon: Tenma Tengai" in The Bungou Stray Dogs Anime Adaptation - Kirana Rizqina; Devinnisa Jehan (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2023)
Typography is the art and technique of arranging letters in a way that makes the written language easier to read and more appealing, display, or distribute. Typography is not limited to Latin or Romaji and is seen in the anime industry, especially anime, where it is used in kanji. Bungou Stray Dogs is an anime that adapts old literature to a younger audience and is a perfect study subject for kanji typography. Despite its manga and anime adaptations, it still sticks to its "old literature" antics. Hence, the focus of the typographic study in this article is solely on the anime version of the Bungou Stray Dogs manga, and specifically on the scene in the anime where the words "rashomon: tenma Tengai" are presented utilizing specific typographic approaches.